Gossypiboma secondary to ovariohysterectomy in a dog - Fabiano da Silva Flores; Carolina Cauduro da Rosa; Graciane Aiello; Anna Vitória Hörbe; Glaucia Denise Kommers; Luís Felipe Dutra Corrêa (Revista MVZ Cordoba)
In veterinary medicine, intra-abdominal foreign bodies are a possible secondary complication of surgical procedures. Gossypiboma is defined as a forgotten textile material after surgery and is considered rare in veterinary medicine because most cases go unreported. The objective of this work is to report the diagnosis of an intra-abdominal gossypiboma in a dog, secondary to theovaryhysterectomy procedure. A 10-year-old Labrador dog had been sterilized about eight years ago. During the clinical analysis, a firm-looking increase in volume was found in the right mesogastric region, without the presence of pain on palpation. For further investigation, the patient was referred for additional imaging tests, such as x-ray and ultrasound. During inspection of the abdominal cavity, a firm circular mass was observed adhered to the omentum and jejunum, caudal to the right kidney. Resection of the mass was performed, and then the mass sample was sent for histopathological examination, which revealed an encapsulated foreign body, consistent with surgical gauze. Gossypiboma is one of the possible complications in surgical procedures in the abdominal cavity, but it is rarely reported in the veterinary literature.